IMPACT OF FDI, GCF, AND EXPORT ON ECONOMIC DEVELOPMENT IN NIGERIA (1980 – 2021) - Ehimare, Anthony Joseph (Digital Repository of Theses, 2023)
The study determined the impact of FDI, GCF, and exports on economic development in Nigeria (1980–2021). A time-series research design and time-series data from secondary sources were used for the study. The dataset ranged from 1980 to 2021. The collected data were analyzed using ordinary least square regression techniques. The autoregressive distributed lag (ARDL) model and the vector error correction model (VECM) were adopted based on the unit root and cointegration tests. The results of the study revealed that the mean values of education, exports, FDI, GCF, and PCI within the period of study were N717.07 billion, N5,715.124 billion, N360.9421 billion, N7,957.668 billion, and N782,855.8 billion, respectively. Furthermore, FDI has a significant relationship with PCI both in the short run and the long run. This implies that the more foreign direct investment (FDI) that is attracted to the country, the better off Nigerians will be. The results posited that GCF had an impact on economic development. This suggests that Nigeria can attain sustained economic development if it pays attention to capital accumulation. The results also suggest that there was no long-run relationship between FDI and educational investment; this may be attributed to continued inconsistency in the educational sector in Nigeria, thereby discouraging potential investors from investing in the educational sector. According to the findings, the GCF had an unstable impact on education, with both positive and negative significant effects. This might be due to the persistent instability in the educational sector. Based on the results, export earnings have an impact on economic development as they serve as a source of foreign exchange earnings and revenue generation for capital investment. Based on the various revelations of the study, it was concluded that the potential contributions of FDI, GCF, and export have not been fully maximized and that FDI, GCF, and export have both short- and long-term impacts on economic development. The study recommended that policy instruments that will drive the improvement of FDI, GCF, and export promotion be implemented in Nigeria.